âARCâSâ : JASA PEMBUATAN DAN PENGEMBANGAN TEKNOLOGI ROBOTIKA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN MENUJU INDONESIA MODERN - Utami, Tifani Galuh; Sari, Afriyani Soraya; Ngilma, NisaÃ¢Â€Â™ Latifatul; Surya B., Tito Garry; Dwi J., Raysita Galuh (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Educational robotics are expected to create the nations next personal creative, innovative and productive person. To begin the application of robotics education, ARCS Electronics comes as a facilitator of learning robotics media providers. Products that we offered are packaged in modular so that easier to understand and allow users to conduct the development and modification against basic forms of the robot. We choose to launch several products of line follower robot. To reach a wider range of customers, we not only provide manufacturing services robot at high school and university levels, but also provide electronic equipment, industrial automation and instrumentation. Keywords: Educational robotics, line follower robot, automation, ARCS Electronic